Antimicrobial resistance and phage sensitivity of Chryseobacterium sp. isolated from diseased rainbow trout (Oncorhynchus mykiss) - Mustafa Ustundag; Berrin Ustundag (Journal of Fisheries, 2025)
This study aimed to isolate and characterize bacteriophages infecting Chryseobacterium sp., an opportunistic pathogen responsible for considerable mortality in rainbow trout (Oncorhynchus mykiss Walbaum, 1792) aquaculture. Chryseobacterium isolates were recovered from diseased trout collected from aquaculture facilities in Mersin and Van (Türkiye) using Anacker–Ordal medium. Identification was performed through API 20E/20ZYM biochemical profiling and 16S rRNA gene sequencing. Antibiotic susceptibility was evaluated by the Kirby–Bauer disk diffusion method following CLSI and EUCAST guidelines. Phages were isolated from water samples via 0.22 μm filtration and purified using the double-layer agar method. Antimicrobial susceptibility testing revealed that Chryseobacterium isolates were sensitive to enrofloxacin, oxolinic acid, and ciprofloxacin, but exhibited pronounced resistance to most β-lactam and aminoglycoside antibiotics. A total of 19 lytic phages (CV1 – CV19) were successfully isolated. They displayed latent periods between 2.5 and 7.5 h and burst sizes ranging from 20 to 235 PFU per cell. The highest burst size and shortest latent period were recorded for the CV5 phage. Adsorption rate constants showed phage-specific variability, with overall values ranging from 1.05×10⁻⁶ to 2.55×10⁻⁶ mL·min⁻¹. Genome sizes were estimated at 48 – 75 kb. TEM revealed typical tailed morphologies consistent with the order Caudovirales. Host range assays showed strong species specificity, with limited cross-activity against Flavobacterium psychrophilum and Enterococcus faecalis. The findings confirm that these phages possess traits favorable for use as eco-friendly biocontrol agents, offering a promising strategy to mitigate Chryseobacterium-associated infections and reduce antibiotic dependence in trout hatcheries.